Proplastids and Juvenile Chloroplasts in the Apical Meristem of Flax - A. Semenova Galina (Journal of Plant Cell Development, 2022)
The apical meristem of plants comprises proplastids and juvenile chloroplasts. This work considered the most initial stages of the transition from proplastid to chloroplast. Ultrastructural analysis of apical meristem sections showed the formation of chloroplast envelope membranes and the synthesis of thylakoid membranes to be independent processes, and the production of thylakoid membrane proteins to directly involve cytoplasm ribosomes.
Keywords: Linum usitatissimum L